Corporate sustainability in entrepreneurial settings: green management and operational fairness as joint drivers of venture competitiveness - Campos, Thalita Láua Reis [UNESP]; Nunhes, Thais Vieira [UNESP]; Harney, Brian; Oliveira, Otavio José de [UNESP] (Emerald, 2023)
Purpose: Considering the characteristics and barriers faced by small and medium enterprises (SMEs) and the need to be competitive in the current scenario of high demand for sustainability, this paper aims to propose drivers for developing corporate sustainability in SMEs based on the most influential theoretical and empirical studies and the authors' experience. Design/methodology/approach: The scientific method used in this study was content analysis of recent literature (2015–2021), specifically the 30 most cited articles on sustainability in SMEs from the Scopus database. This methodological approach has already been tested and validity by other scientific studies. From this content analysis, elements for the development of sustainability in SMEs were identified. Subsequently, in light of the authors' experience, these elements were grouped by affinity, giving rise to the drivers that aim to guide owners and managers of SMEs in the transition to sustainability. Findings: The major finding of this paper is the proposition of drivers for the development of sustainability in SMEs. They were proposed considering the reality of these companies to be adequate to their resources and structure and to be simple to apply. Thus, these drivers guide the owners and managers of SMEs in actions that make them more prosperous, fair and green and, consequently, more competitive. Originality/value: This work contributes theoretically to deepening the recent body of knowledge on sustainability in SMEs and fills the gap that indicates the need for accessible and flexible management solutions oriented to the development of sustainability in SMEs.
Keywords: Corporate sustainability; Small and medium enterprises (SMEs); Small business; Sustainable development